Causal Association Between Periodontitis and Type 2 Diabetes: A Bidirectional Two-Sample Mendelian Randomization Analysis - Wang, Yong-Bo; Yan, Si-Yu; Li, Xu-Hui; Huang, Qiao; Luo, Li-Sha; Wang, Yun-Yun; Huang, Jiao; Jin, Ying-Hui; Zeng, Xian-Tao (Frontiers in Genetics, 2022)
Background: Previous observational studies have reported a bidirectional association between periodontitis and type 2 diabetes, but the causality of these relationships remains unestablished. We clarified the bidirectional causal association through two-sample Mendelian randomization (MR). Methods: We obtained summary-level data for periodontitis and type 2 diabetes from several published large-scale genome-wide association studies (GWAS) of individuals of European-ancestry. For the casual effect of periodontitis on type 2 diabetes, we used 5 independent single-nucleotide polymorphisms (SNPs) specific to periodontitis from 3 GWAS. The summary statistics for the associations of exposure-related SNPs with type 2 diabetes were drawn from the GWAS in Diabetes Genetics Replication and Meta-analysis (DIAGRAM) Consortium and FinnGen consortium R5 release, respectively. For the reversed causal inference, 132 and 49 SNPs associated with type 2 diabetes from the DIAGRAM consortium and FinnGen consortium R5 release were included and the summary-level statistics were obtained from the Gene-Lifestyle Interactions in Dental Endpoints consortium. Multiple approaches of MR were carried-out. Results: Periodontitis was not causally related with the risk of type 2 diabetes (all P > 0.05). And no causal effect of type 2 diabetes on periodontitis was found (all P > 0.05). Estimates were consistent across multiple MR analyses. Conclusions: This study based on genetic data does not support a bidirectional causal association between periodontitis and type 2 diabetes.